A Systematic Review and Meta-analysis of the Association Between ACTN3 R577X Genotypes and Performance in Endurance Versus Power Athletes and Non-athletes - El Mokhtar El Ouali; Benjamin Barthelemy; Juan Del Coso; Anthony C. Hackney; Ismail Laher; Karuppasamy Govindasamy; Abdelhalem Mesfioui; Urs Granacher; Hassane Zouhal (SpringerOpen, 2024)
Abstract Background Previous studies reported differences in genotype frequency of the ACTN3 R577X polymorphisms (rs1815739; RR, RX and XX) in athletes and non-athletic populations. This systematic review with meta-analysis assessed ACTN3 R577X genotype frequencies in power versus endurance athletes and non-athletes. Methods Five electronic databases (PubMed, Web of Science, Scopus, Science Direct, SPORTDiscus) were searched for research articles published until December 31st, 2022. Studies were included if they reported the frequency of the ACTN3 R577X genotypes in power athletes (e.g., weightlifters) and if they included a comparison with endurance athletes (e.g., long-distance runners) or non-athletic controls. A meta-analysis was then performed using either fixed or random-effects models. Pooled odds ratios (OR) were determined. Heterogeneity was detected using I2 and Cochran's Q tests. Publication bias and sensitivity analysis tests were computed. Results After screening 476 initial registrations, 25 studies were included in the final analysis (13 different countries; 14,541 participants). In power athletes, the RX genotype was predominant over the two other genotypes: RR versus RX (OR 0.70; 95% CI 0.57-0.85, p = 0.0005), RR versus XX (OR 4.26; 95% CI 3.19-5.69, p < 0.00001), RX versus XX (OR 6.58; 95% CI 5.66-7.67, p < 0.00001). The R allele was higher than the X allele (OR 2.87; 95% CI 2.35-3.50, p < 0.00001) in power athletes. Additionally, the frequency of the RR genotype was higher in power athletes than in non-athletes (OR 1.48; 95% CI 1.25-1.75, p < 0.00001). The RX genotype was similar in both groups (OR 0.84; 95% CI 0.71-1.00, p = 0.06). The XX genotype was lower in power athletes than in controls (OR 0.73; 95% CI 0.64-0.84, p < 0.00001). Furthermore, the R allele frequency was higher in power athletes than in controls (OR 1.28; 95% CI 1.19-1.38, p < 0.00001). Conversely, a higher frequency of X allele was observed in the control group compared to power athletes (OR 0.78; 95% CI 0.73-0.84, p < 0.00001). On the other hand, the frequency of the RR genotype was higher in power athletes than in endurance athletes (OR 1.27; 95% CI 1.09-1.49, p = 0.003). The frequency of the RX genotype was similar in both groups (OR 1.07; 95% CI 0.93-1.24, p = 0.36). In contrast, the frequency of the XX genotype was lower in power athletes than in endurance athletes (OR 0.63; 95% CI 0.52-0.76, p < 0.00001). In addition, the R allele was higher in power athletes than in endurance athletes (OR 1.32; 95% CI 1.11-1.57, p = 0.002). However, the X allele was higher in endurance athletes compared to power athletes (OR 0.76; 95% CI 0.64-0.90, p = 0.002). Finally, the genotypic and allelic frequency of ACTN3 genes were similar in male and female power athletes. Conclusions The pattern of the frequencies of the ACTN3 R577X genotypes in power athletes was RX > RR > XX. However, the RR genotype and R allele were overrepresented in power athletes compared to non-athletes and endurance athletes. These data suggest that the RR genotype and R allele, which is associated with a normal expression of α-actinin-3 in fast-twitch muscle fibers, may offer some benefit in improving performance development in muscle strength and power.